A glance at takeovers models in Australia, Malaysia, Singapore and the United Kingdom - Mohd Ali, Haitham Abdulkareem; Salman, Mohammed Jamiu; Ambaras Khan, Mushera Bibi (PKP Publishing Services, 2016)
This paper sheds the light on multiple models of takeover offers in the following jurisdictions, Australia, Malaysia, Singapore and the United Kingdom. The paper attempts to examine and investigate these models through a classical process of understanding the basic historical background and the facts about the different models of takeover offers. This study employs a qualitative research methodology in a form of comparative study in which the legislations in these jurisdictions including their guidelines and strategies surrounding these models were examined, in addition to the characteristics of each model over the others. In conclusion, it was observed that there is a great similarity between these models, more specifically between the Malaysian and Singaporean model on one hand, and the United Kingdom (UK) and the Australian models on the other.